Antimicrobial susceptibility of Shigella flexneri and S. dysenteriae isolated from stool specimens of patients with bloody diarrhoea in Mwansa, Tanzania - Temu, M M; Kaatano, G M; Miyaye, N D; Buhalata, S N; Shushu, M-L; Kishamawe, C; Changalucha, J M (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp.186-189